Effects of welding parameters on the angular distortion of welded steel plates - (:unkn) unknown (My University, 2022)
In a welding process, distortion is inevitable and causes a significant problem. Distortion could be minimized up to a specific limit by controlling the welding parameters. The expansion and contraction of the welding metal and the adjacent base metal during the heating and cooling cycles of the welding process create thermal stresses and angular distortion in a welding joint. The welding parameters determine the geometry of a weld bead. The form of the weld bead is vital in the angular distortion of butt welded plates. This article discusses the influence of some flux-cored arc welding process parameters such as shielding gas flow rate, weaving motion of welding electrodes, and torch angle on bead profile and angular distortion of St 37 steel plates of 10 mm thickness. The angular distortion decreases with the torch angle, but it increases with the gas flow rate. The electrode weaving motion consists of three components: the designed weld width, the vertical motion period in the welding direction, and the lateral motion speed normal to the welding direction. The angular distortion decreases with the weld width and the vertical motion period but decreases with the lateral speed.
Keywords: Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Chemistry; Biochemistry; Alcaloides; Natural Sciences; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); Kimya (çeşitli); Genel Kimya; Fizik Bilimleri; Chemistry (miscellaneous); General Chemistry; Physical Sciences; FCAW; angular distortion; gas flow rate; torch angle; weaving motion of welding electrodes; STAINLESS-STEEL; OPTIMIZATION; FCAW; angular distortion; gas flow rate; torch angle; weaving motion of welding electrodes